Prediction of sound transmission loss of hemispherical shell using statistical energy analysis and its experimental validation. (30th November 2022) - Gupta, Pavan; Parey, Anand
Highlights: Prediction of sound transmission loss of hemispherical shell using statistical energy analysis. Measurement of sound transmission loss of hemispherical shell using the sound intensity technique. Measurement of dissipation loss factor of hemispherical shell using the decay rate technique. Measurement of natural frequencies of the hemispherical shell using experimental modal analysis test. Abstract: The hemispherical shells are broadly used in many industries and applications such as aerospace, submarines, tanks, and architectural structures. Sound transmission loss prediction of such structures is essentially required during the design and assessment phases from the acoustic point of view. In the present paper, sound transmission loss of the hemispherical shell is predicted analytically and validated experimentally. The Statistical energy analysis (SEA) technique is employed to formulate an analytical model for computing the sound transmission loss of a hemispherical shell across a wide frequency range. The sound intensity experimental method was used to verify the proposed SEA formulation. The analytical predictions and the measured transmission loss were found to be in good agreement. Based on the proposed SEA model, the influence of design parameters such as the absorption coefficient, thickness, radius, and different materials on the transmission loss was investigated.